Low-cost energy conservation measures power saving impact on electronic appliances usage - Tyagi, Ruchi; Ali, Shaikh Shamser; vishwaakarma, Suresh (Institute of Advanced Engineering and Science, 2023)
Energy conservation measures use less energy to reduce costs and the environmental impact without compromising the consumer’s comfort level. Low-cost energy conservation measures play a critical role in power saving on the usage of electronic devices. The paper compares two different facilities using air-conditioning applications to study the impacts of low-cost energy conservation measures (LCECM) in real-time operations. The effect was recorded at both facilities by lowering the air-conditioning running time and increasing its set temperature ensuring that there was no compromise in occupants’ comfort level. As per international performance measurement and verification (IPMV) protocol A, data analysis was done using pre- and post-experiment readings. IPMVP output was analyzed more by running a t-Test in the SPSS software. Results indicated energy conservation with a cumulative impact on carbon footprint, environment, and cost of importing fossil fuel. The limitations of this study are that the energy conservation measurements were made with limited facilities and respondents' restrictions.